Viral Affects and Economies of Desire in Hirotaka Tobi's "Autogenic Dreaming". Issue 1 (April 2019) - Dumas, Raechel
Abstract : This essay provides a close reading of Hirotaka Tobi's short story "Autogenic Dreaming, " concentrating on its nuanced engagement with the trajectory of Japanese literary sensibilities in a present marked by the decline of modern narratives of history, identity, and nation. With attention to its innovative content and form, it considers the text's use of the theoretically limitless domain of cyberspace as a site for elaborating the possibility for literature to act in accordance with more recently emergent technologies of representation by leveraging the symbolic field of language to generate unanticipated meanings and solicit transformative encounters. Ultimately, it argues that "Autogenic Dreaming" not only offers a speculative vision of a technologically mediated future, but also speaks to the futurity of Japanese literature itself, exemplifying what might be termed an "emergent fiction" that fulfills a growing demand for literature that enables us to experience novel constellations of subjectivity, interaction, and desire.